Analisis Pengaruh Pertumbuhan Ekonomi, Pendidikan, Pengangguran Dan Inflasi Terhadap Kemiskinan Di Indonesia Tahun 1996-2014 - Rahmaniar, Nizma Karima; , Drs. Yuni Prihadi Utomo, MM (2017)
Data used in this research is secondary data, poverty, economic growth, education, unemployment, and inflation in Indonesia. the analytical method used was Ordinary Least Squares (Ols) is to determine the direction and magnitude of the effect of one independent variable (independent) on the dependent variable (dependent). The resulth of this study can be concluded that the variable growt has significant influence on poverty with the coefficient value of -0.035144. the same is also available on education variables that had a significant influence on poverty with the coefficient value of -0.008560. the same is also available on the inflation variable that has a significant influence on poverty with the coefficient value of -0.005461. while the variable unemployment has a negative effect on poverty with a coefficient of 0.00556.